Convergence, income distribution, and the economic crisis in Europe - Ville Kaitila (The Research Institute of the Finnish Economy (ETLA), 2013)
We analyse the Sigma convergence (standard deviation divided by average) of purchasing power adjusted GDP per capita and GDP per hour worked in the European Union. We also link the development in income distribution as measured by Gini coefficients to convergence. With short pauses, there has been a long term trend of GDP per capita convergence in the European Union after 1960. The Great Recession was a shock to the development, and convergence within the EU-15 has suffered considerably. The largest relative declines have occurred in Cyprus, Greece, Italy, Portugal and Spain. On the other hand, the ex-transition countries have mostly continued their catching up. Historically, convergence in the EU has been faster when aggregate GDP growth has been faster. We also find that income disparities measured by Gini coefficients are negatively related to GDP per capita levels. Convergence was not correlated with changes in income distribution in 2000–2011 except for a group of six catching-up countries where we find a positive relation. We also find that there has occurred Sigma convergence in national Gini coefficients
Keywords: F15; F43; O15; O47; 330; EU; GDP per capita; productivity; Sigma convergence; Gini coefficient